2010
DOI: 10.1002/jbmr.225
|View full text |Cite
|
Sign up to set email alerts
|

An essential role of discoidin domain receptor 2 (DDR2) in osteoblast differentiation and chondrocyte maturation via modulation of Runx2 activation

Abstract: Discoidin domain receptor 2 (DDR2) belongs to receptor tyrosine kinase (RTK) family and is activated by collagen binding. Although the bone defects in Ddr2 null mice have been reported for a decade, the molecular mechanism remains unclear. This study sought to investigate the function and detailed mechanism of DDR2 in osteogenic and chondrogenic differentiation. Herein we found that in preosteoblastic cells, DDR2 activation was enhanced by osteogenic induction but was not paralleled with the alteration of DDR2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 99 publications
(97 citation statements)
references
References 72 publications
5
92
0
Order By: Relevance
“…DDR2 was the only gene with newly acquired mutations in the metachronous tumors of 2 patients, PY-3 and PY-8 (Table 4 and Figures 3 and 4). DDR2 encodes the discoidin domain receptor 2, which is a collagen-stimulated receptor tyrosine kinase implicated in a wide range of processes including regulation of epithelialto-mesenchymal transition (EMT) and osteogenic/chondrogenic differentiation (43,44). Although the functional mechanisms of DDR2 expression and/or mutation in disease are incompletely understood, alterations in DDR2 have been implicated in cellular adhesion, migration, invasion, and metastasis in prostate cancer, breast cancer, and recently, HNSCC (45)(46)(47)(48).…”
Section: Resultsmentioning
confidence: 99%
“…DDR2 was the only gene with newly acquired mutations in the metachronous tumors of 2 patients, PY-3 and PY-8 (Table 4 and Figures 3 and 4). DDR2 encodes the discoidin domain receptor 2, which is a collagen-stimulated receptor tyrosine kinase implicated in a wide range of processes including regulation of epithelialto-mesenchymal transition (EMT) and osteogenic/chondrogenic differentiation (43,44). Although the functional mechanisms of DDR2 expression and/or mutation in disease are incompletely understood, alterations in DDR2 have been implicated in cellular adhesion, migration, invasion, and metastasis in prostate cancer, breast cancer, and recently, HNSCC (45)(46)(47)(48).…”
Section: Resultsmentioning
confidence: 99%
“…DDR2 signals to ERK1/2 and p38, but not JNK, in chondrocytes [106] but uses p38 and JNK, and not ERK1/2, in transfected embryonic kidney cells [107]. In osteoblasts, DDR2 signalling activates the transcription factor Runx 2, but conflicting data exist whether this is via p38 MAP kinase or ERK1/2 [108,109].…”
Section: Ddr Signallingmentioning
confidence: 99%
“…MMP-13 and GAPDH primer sequences were the same as described previously [9,21]. The procedures of RNA isolation and real time PCR were described in Supplementary data.…”
Section: Real Time Pcrmentioning
confidence: 99%
“…In our previous study, DDR2 was demonstrated to play crucial roles in the differentiation of pre-osteoblastic MC3T3-E1 cells [9]. Therefore, this cell line was utilized to measure the effects of Cbl-b knockdown on the ubiquitination and degradation of endogenous DDR2 as well as on the expression level of its downstream target.…”
Section: Cbl-b Overexpression Decreases the Protein Stability Of Ddr2mentioning
confidence: 99%
See 1 more Smart Citation